Accurate and Sensitive Determination of Atraton in Dried Tomato and Corn Flour by High-Performance Liquid Chromatography (HPLC) and Characterization of Its Stability in Gastric Conditions and by Ultraviolet Radiation - Ozdogan, Nizamettin; Yener, Berrin; Zaman, Buse Tugba; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2020)
Atraton determination in dried tomato soup and corn flour samples was performed using high performance liquid chromatography with ultraviolet-visible detection (HPLC). Atraton was eluted through a C18 column with 70:30 (v/v) pH 6.0 acetate buffer:acetonitrile as the mobile phase. The detection was performed at the 220 nm analytical wavelength. The limit of detection and quantification values were determined to be 0.028 and 0.095 mg/L, respectively, from the linear range determined to be from 0.10 to 20 mg/L. The correlation coefficient (0.9997) and percent relative standard deviation (3.9%) calculated for the lowest calibration concentration revealed that the method provided high linearity and repeatability, respectively. The applicability and accuracy of the method were investigated by applying the optimum procedure to dried tomato soup and corn flour matrices. Satisfactory recovery values were obtained between 90 and 108%, showing that atraton was accurately quantified in real samples with complex matrices. Atraton was subjected to simulated gastric conditions for 210 minutes and exposed to ultraviolet radiation for 360 minutes to determine its stability. However, no degradation was observed under either of these conditions.
Keywords: Atraton; herbicide; high performance liquid chromatography (HPLC); synthetic gastric fluid; ultraviolet degradation; SOLID-PHASE EXTRACTION; ENVIRONMENTAL WATER SAMPLES; TRIAZINE HERBICIDES; GAS-CHROMATOGRAPHY; MICROEXTRACTION; MILK; METABOLITES; PESTICIDES; LEVEL; Chemistry